Teori dan Implementasi Gaya Kepemimpinan Kepala Sekolah - Lumban Gaol, Nasib Tua (Kelola: Jurnal Manajemen Pendidikan, 2017)
Indonesia faces many problems in education. The main problem is raised from the low ability of the headmaster to manage the school. This is related to leadership style. This study aims to explore leadership styles in the field of education and discusses how headmasters should apply leadership styles in schools. Some appropriate leadership styles are applied by the headmaster consisting of (1) managerial leadership, (2) transformational leadership, (3) transactional leadership, (4) instructional leadership and (5) positive leadership. Therefore, the headmaster not only applies a leadership style while managing the school but must be able to combine and contextualize leadership styles based on the need to obtain school goals.